Calculate the rates of Runoff and Recharge in the Al-Karma Area, East of Anbar Governorate/ western Iraq - Al-Halbousi, A. S; Al-Kubaisi , Q. Y (Iraqi Journal of Science, 2026)
This study aims to estimate the runoff and recharge values in the Al-Karma area, located East of Anbar Governorate, western Iraq. Climate data were collected from 1981 to 2023 at Baghdad Airport and Ramadi stations. The data include six parameters. The monthly average of Temperature, Relative humidity, Wind speed, Sunshine, and Evaporation in both stations (Baghdad and Ramadi) were 23.50C-22.40C, 43.07 %-50.68 %, 3.18 m/s -2.29 m/s, 8.6 h/day -8.7 h/day, and 262.3 mm-223.5 mm with total of rainfall 124.7mm and110.6mm in both stations (Baghdad and Ramadi), respectively. There is a clear variation in climatic data between the two stations. The results show that the highest parameters of (Temperature, Rainfall, Wind speed, and Evaporation) were recorded in Baghdad stations. In contrast, other parameters (Relative humidity, Sunshine) were recorded at the highest values in Ramadi stations. This variation in climatic parameters is due to elevation, Agricultural desert nature, and human activity. In this study, the Runoff and Recharge values were estimated in the study area. The results show that the runoff and recharge values in both stations (Baghdad and Ramadi) were 17.64 mm, 9.03 mm, and 13.42 mm, 9.98 mm respectively, the average calculation for the two stations was approved, which will represent the surface runoff and groundwater recharge for the Al-Karma area, which is (13.34) mm and (11.7) mm, respectively.  Finally, the study area was classified as Arid and sub-arid depending on the climate data from Baghdad and Ramadi stations.